A Discussion on the Phonon Density of States of Amorphous Germanium for the Infrared Range - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
A theoretical formulation for the phonon density of states of amorphous germanium in the infrared range is proposed. This formulation is based upon the quasi-harmonic approximation and is compared with previous results.